PRODUCTION OF DOMESTIC FEED USING NON-TRADITIONAL TYPES OF RAW MATERIALS PROCESSING AND FOOD PRODUCTION - ZH. S. Alimkulov; M. T. Veliamov; T. M. Sarmankulov; T. M. Zhumalieva (Алматы технологиялық университетінің хабаршысы, 2021)
The article considers the possibility of using as a raw material for the production of feed waste processing of grapes - grape marc and natural mineral sorbent - vermiculite. The chemical composition of forage meal from grape marc and vermiculite is given. The data showed that the waste obtained in the processing of grapes in its chemical composition comply with the standards imposed on the components of animal feed. However, the physico-mechanical properties and the hygroscopicity of grape marc do not meet the requirements of feed milling. Introduction to the composition of the feed additive vermiculite feed allows you to adjust their properties.